Effects of epigallocatechin-3-gallate and nano-hydroxyapatite on bone morphogenetic protein-2 expression and formation of odontoblast-like cells in rats with inflamed dental pulp - Kun Ismiyatin; Adioro Soetojo; Sukaton; Tengku Natasha Eleena binti Tengku Ahmad Noor; Paramita Tanjung Sari; Fridianty Anggraeni; Nisrina Qurrota Aini; Nadia Dwi Maharani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2026)
Background: Epigallocatechin-3-gallate (EGCG) and nano-hydroxyapatite (n-HA) have demonstrated promising bioactive properties for use in vital pulp therapy; EGCG exhibits antioxidant and immunomodulatory effects, whereas n-HA promotes osteogenic differentiation and dentin bridge formation. Purpose: To evaluate the combined effect of EGCG and n-HA on the expression of bone morphogenetic protein-2 (BMP-2) and the differentiation of odontoblast-like cells (OLCs) in rats with inflamed dental pulp. Methods: Fifty-four Wistar rats (Rattus norvegicus) were randomly assigned to six groups and anesthetized. Class I cavities were prepared on the occlusal surface of the maxillary right first molar using a 0.84-mm-diameter low-speed diamond bur, followed by pulp chamber perforation with a dental probe. The exposed pulps were treated with n-HA, EGCG, or a combination of both. Cavities were sealed using resin-modified glass ionomer cement; BMP-2 and OLC expression levels were evaluated on days 7 and 14. Results: On day 7, the mean number of OLCs was lowest in the n-HA group (2.667 ± 1.225) and highest in the combination group (8.889 ± 1.691). Tukey’s honestly significant difference test indicated significant differences between the combination group and both the n-HA and EGCG groups (P < 0.05). By day 14, the mean number of OLCs increased in all groups, with the combination group showing the highest value (12.443 ± 2.167). The Wilcoxon Mann–Whitney U test confirmed significant intergroup differences (P < 0.05). Conclusion: The combination of EGCG and n-HA enhances BMP-2 expression levels and OLC differentiation, supporting its potential as a biologically active pulp capping material.